2003
DOI: 10.1007/978-3-540-39701-4_7
|View full text |Cite
|
Sign up to set email alerts
|

Non-rigid Registration of Serial Intra-operative Images for Automatic Brain Shift Estimation

Abstract: Measurement of intra-operative brain motion is important to provide boundary conditions to physics-based deformation models that can be used to register pre-and intra-operative information. In this paper we present and test a technique that can be used to measure brain surface motion automatically. This method relies on a tracked laser range scanner (LRS) that can acquire simultaneously a picture and the 3D physical coordinates of objects within its field of view. This reduces the 3D tracking problem to a 2D n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The first is to use registration techniques based on intraoperative image data. Modalities such as iMR and iUS but also Laser Range Scanner (LRS) and Stereo Vision are used to acquire intraoperative image data [ 49 52 , 56 , 59 70 , 77 , 79 , 80 , 87 ]. Usually, LRS and Stereo Vision are used to acquire the intraoperative cortical surface deformation which is then integrated into a precomputed patient specific biomedical model in order to estimate the volumetric deformation.…”
Section: Compensation For Intraoperative Brain Deformationmentioning
confidence: 99%
See 3 more Smart Citations
“…The first is to use registration techniques based on intraoperative image data. Modalities such as iMR and iUS but also Laser Range Scanner (LRS) and Stereo Vision are used to acquire intraoperative image data [ 49 52 , 56 , 59 70 , 77 , 79 , 80 , 87 ]. Usually, LRS and Stereo Vision are used to acquire the intraoperative cortical surface deformation which is then integrated into a precomputed patient specific biomedical model in order to estimate the volumetric deformation.…”
Section: Compensation For Intraoperative Brain Deformationmentioning
confidence: 99%
“…Usually, LRS and Stereo Vision are used to acquire the intraoperative cortical surface deformation which is then integrated into a precomputed patient specific biomedical model in order to estimate the volumetric deformation. However, these papers [ 67 70 , 77 , 79 , 80 ] are still categorized as registration-based method, because they only presented the registration approaches which register the intraoperative surface data either with preoperative MR or between data acquired at different time points. The model-based purpose is not described directly in these works; therefore the purpose of these works is not clear without any additional knowledge.…”
Section: Compensation For Intraoperative Brain Deformationmentioning
confidence: 99%
See 2 more Smart Citations
“…Image deformation in the ABA is provided by radial-basis functions (RBFs), whose coefficients are optimized for registration. The robustness and accuracy of the ABA on in vivo texture images from the LRS device has been explored and verified in Duay et al [28] and an example registration of in vivo LRS texture images is shown in Fig. …”
Section: B Shift-tracking Protocolmentioning
confidence: 99%